Constituting Histories Through Culture In Iraqi Kurdistan. (1st July 2018) - Cockrell-Abdullah, Autumn
Abstract : Today, Kurds in Northern Iraq are employing a narrative of the Kurdish nation that bears strong ethnic roots and includes the memory of the victimization of the Kurdish nation. This essay examines the repurposing of the National Museum at Amna Suraka in Iraqi Kurdistan, from its former role as a Ba'ath site for detention, torture and execution, into a site for the preservation of Kurdish history and culture. In doing so, this essay locates the National Museum at Amna Suraka, and its role as a museum for Kurdish history and culture and as a national memorial, within the historical context of the Iraqi state. Such an examination, demonstrates the intersectional nature of the struggle for national identity within Iraqi Kurdish society, non-Kurds outside of Iraqi Kurdistan and for transnational Kurdish publics.